Electroanatomical Voltage Mapping to Distinguish Right-Sided Cardiac Sarcoidosis From Arrhythmogenic Right Ventricular Cardiomyopathy - Hoogendoorn, Jarieke C; Sramko, Marek; Venlet, Jeroen; Siontis, Konstantinos C; Kumar, Saurabh; Singh, Robin; Nakajima, Ikutaro; Piers, Sebastiaan R D; de Riva Silva, Marta; Glashan, Claire A; Crawford, Thomas; Tedrow, Usha B; et al. (JACC. Clinical electrophysiology, 2020)
OBJECTIVES: This study sought to investigate the value of electroanatomical voltage mapping (EAVM) to distinguish cardiac sarcoidosis (CS) from arrhythmogenic right ventricular cardiomyopathy (ARVC) in patients with ventricular tachycardia from the right ventricle (RV). BACKGROUND: CS can mimic ARVC. Because scar in ARVC is predominantly subepicardial, this study hypothesized that the relative sizes of endocardial low bipolar voltage (BV) to low unipolar voltage (UV) areas may distinguish CS from ARVC. METHODS: Patients with CS affecting the RV (n = 14), patients with gene-positive ARVC (n = 13), and a reference group of patients without structural heart disease (n = 9) who underwent RV endocardial EAVM were included. RV region-specific BV and UV cutoffs were derived from control subjects. In CS and ARVC, segmental involvement was determined and low-voltage areas were measured, using <1.5 mV for BV and <3.9 mV, <4.4 mV, and <5.5 mV for UV. The ratio between low BV and low UV area was calculated generating 3 parameters: Ratio3.9, Ratio4.4 and Ratio5.5, respectively. RESULTS: In control subjects, BV and UV varied significantly among RV regions. The basal septum was involved in 71% of CS patients and in none of ARVC patients. Ratio5.5 discriminated CS from ARVC the best. An algorithm including Ratio5.5 ≥0.45 and basal septal involvement identified CS with 93% sensitivity and 85% specificity. This was validated in a separate population (CS [n = 6], ARVC [n = 10]) with 100% sensitivity and 100% specificity. CONCLUSIONS: EAVM provides detailed information about scar characteristics and scar distribution in the RV. An algorithm combining Ratio5.5 (area BV <1.5 mV/area UV <5.5 mV) and bipolar basal septal involvement allows accurate diagnosis of (isolated) CS in patients presenting with monomorphic ventricular tachycardia from the RV.
Keywords: arytmogenní dysplazie pravé komory; elektrokardiografie; electroanatomical voltage mapping; right ventricle; Humans; arrhythmogenic right ventricular cardiomyopathy; lidé; Electrophysiologic Techniques, Cardiac; Arrhythmogenic Right Ventricular Dysplasia; Sarcoidosis; ventricular tachycardia; sarkoidóza; elektrofyziologické techniky kardiologické; cardiac sarcoidosis; Tachycardia, Ventricular; komorová tachykardie; Electrocardiography